Ce-Al-MCM-41: an efficient catalyst for Mukaiyama-Michael reaction - Kalita, Pranjal; Kumar, Rajiv (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
The activity of cerium containing Al-MCM-41 mesoporous materials has been studied for carbon-carbon bond formation reaction like Mukaiyama-Michael reaction under mild liquid phase conditions. The catalysts were synthesized by hydrothermal method at 383 K for 24-36 h in Teflon-lined autoclave and characterized thoroughly by XRD, UV-VIS, TEM, EPR, XPS, (27)Al NMR, NH(3)-TPD, pyridine-IR and AAS in order to obtain well-ordered M41S type materials. The Mukiayama-Michael reactions between silyl enol ether and alpha,beta-unsaturated ketones give Michael product in very good yields (100% selectivity). The catalysts were reusable.